The Synergy Trap : How Companies Lose the Acquisition Game - Mark L. Sirower (USA Simon & Schuster Australia, 1997)
This groundbreaking study, cited in Business Week, explains how companies often pay too much--and never realize goals of increased performance and market strength--in their quests to acquire other companies. By examining such variables as method of payment and strategic relatedness, Sirower provides the first formal definitions for synergies. 10 illustrations.